FoxO1 Mediates PTEN Suppression of Androgen Receptor N- and C-Terminal Interactions and Coactivator Recruitment - Ma, Qiuping; Fu, Wei; Li, Pengfei; Nicosia, Santo V.; Jenster, Guido; Zhang, Xiaohong; Bai, Wenlong (Molecular endocrinology (Baltimore, Md.), 2009)
Abstract FoxO (mammalian forkhead subclass O) proteins are transcription factors acting downstream of the PTEN (phosphatase and tensin homolog deleted on chromosome 10) tumor suppressor. Their activity is negatively regulated by AKT-mediated phosphorylation. Our previous studies showed that the transcriptional activity of the androgen receptor (AR) was inhibited by PTEN in an AKT-sensitive manner. Here, we report the repression of the activity of the full-length AR and its N-terminal domain by FoxO1 and the participation of FoxO1 in AR inhibition by PTEN. Ectopic expression of active FoxO1 decreased the transcriptional activity of AR as well as androgen-induced cell proliferation and production of prostate-specific antigen. FoxO1 knock down by RNA interference increased the transcriptional activity of the AR in PTEN-intact cells and relieved its inhibition by ectopic PTEN in PTEN-null cells. Mutational analysis revealed that FoxO1 fragment 150–655, which contains the forkhead box and C-terminal activation domain, was required for AR inhibition. Mammalian two-hybrid and glutathione-S-transferase pull-down assays demonstrated that the inhibition of AR activity by PTEN through FoxO1 involved the interference of androgen-induced interaction of the N- and C-termini of the AR and the recruitment of the p160 coactivators to its N terminus and to the androgen response elements of natural AR target genes. These studies reveal new mechanisms for the inhibition of AR activity by PTEN-FoxO axis and establish FoxO proteins as important nuclear factors that mediate the mutual antagonism between AR and PTEN tumor suppressor in prostate cancer cells.